Collaborative Leadership in Education: Increasing Teacher Participation in Decision Making - Khofi, Mohammad Bilutfikal (Journal of Loomingulisus ja Innovatsioon, 2024)
Collaborative leadership requires the active involvement of teachers in the decision-making process so that they can participate rationally and responsibly. This study uses a qualitative method with a case study approach. The purpose of this study is to explore and analyze the application of collaborative leadership in increasing teacher participation in decision-making at Madrasah Aliyah ATQIA Bondowoso. Data were collected through in-depth interviews and participant observation. Data were analyzed using the Miles and Huberman model, which includes the process of data reduction, data presentation, and conclusion. The results of this study found that collaborative leadership at Madrasah Aliyah ATQIA in increasing teacher participation in decision-making was carried out in several ways, namely: building an open communication forum, holding discussion groups with anjangsana format, encouraging teacher initiatives through Idea Bank, recognizing and appreciating teacher contributions, and integrating their input into policies. This has proven effective in increasing teachers’ motivation, sense of belonging, and commitment to the school.